How far does Choice Theory Succeed, Within Classics, as a Form of Differentiation in the Classroom? - Jessica Platt (The Journal of Classics Teaching, 2018)
This therefore suggests that the Year 11 class will not concur with studies to suggest that choice provides students with the motivation to achieve, rather that the boys are more likely to obstruct their learning by choosing the easier choice of task. The second class is a Year 9 Latin class, and there is a lower percentage of mixed-ability students in this class. Owing to this, the class will, I hope, further demonstrate whether choice in the classroom is linked to motivation and high performance. The reason why I have chosen two different classes and subjects is because, generally, the atmosphere in the classes and the preparation of lessons in each are very different from each other. It will therefore be worthwhile to determine how choice theory works in both instances.